2016
DOI: 10.1111/1744-9987.12432
|View full text |Cite
|
Sign up to set email alerts
|

Citrate Extended High Cut‐Off Hemodiafiltration for Renal Recovery in Patients With Multiple Myeloma

Abstract: We proposed a combination of convective and diffusive transport mechanisms as high cut-off (HCO) post-dilution hemodiafiltration dialysis technique to optimize serum immunoglobulin free light chains (FLCs) removal which may improve dialysis dependent renal failure in patients with multiple myeloma. To reduce bleeding risk regional citrate anticoagulation was successfully used for the first 7 h followed by 1 h anticoagulant-free hemodiafiltration to avoid citrate accumulation. We retrospectively assessed the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In comparison with calcium balance, magnesium balance during intermittent HD has been studied in less detail: there is some data on the effect of RCA on serum magnesium levels in intermittent HD [12,21], but the topic has received scant attention. [23] It is important to emphasize that hypomagnesemia is not to be ignored, since some cohort studies have reported that lower serum magnesium levels are associated with an increased risk of all-cause and cardiovascular mortality among HD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with calcium balance, magnesium balance during intermittent HD has been studied in less detail: there is some data on the effect of RCA on serum magnesium levels in intermittent HD [12,21], but the topic has received scant attention. [23] It is important to emphasize that hypomagnesemia is not to be ignored, since some cohort studies have reported that lower serum magnesium levels are associated with an increased risk of all-cause and cardiovascular mortality among HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Given all its benefits, citrate has already become the standard anticoagulant in acute kidney injury requiring continuous renal replacement therapy, not only for adults [7], but also for pediatric patients [8]. Furthermore, RCA is being increasingly used in various intermittent HD modalities, such as chronic high-flux [6,9,10] and lowflux HD [11], hemodiafiltration with a high cut-off (Ther-alite®) membrane [12], and single-needle HD [13].…”
Section: Introductionmentioning
confidence: 99%
“…Blood and dialysate flow were set to 250–350 and 500 ml/min, respectively, with ultrafiltration performed according to clinical needs. There is also a study that applied HCO membranes in post-dilution hemodiafiltration in MM patients with AKI ( 52 ).…”
Section: Protocols For Hco-hdmentioning
confidence: 99%
“…[8][9][10] Conventional HD with High-flux (HF) membranes eliminates such mediators insufficiently, their accumulation may lead to elevated synthesis of hepatic CRP. 11,12 High cut-off (HCO) membranes, 13,14 especially those with a nominal cut off point of 45 kDa (HCO1100, Gambro), have been successfully employed for the treatment of light-chain nephropathy in patients with multiple myeloma [15][16][17][18][19][20] and of septic shock. 21,22 Their ability to remove large quantities of inflammation mediators makes the HCO membranes a promising tool for chronic HD patients with elevated CRP level.…”
Section: Introductionmentioning
confidence: 99%